1354 USING REALIST PROGRAMME THEORY TO DESIGN A NEW INTERVENTION FOR IMPROVING RECOVERY AFTER DELIRIUM. (16th January 2023) - Raghuraman, S; Richards, E; Morgan-Trimmer, S; Clare, L; Anderson, R; Goodwin, V; Allan, L
Abstract: Introduction: People who recover poorly after delirium are likely to require an increased level of care. It is presently unknown whether interventions to improve recovery after delirium are effective and cost-effective. This research aimed to develop a programme theory to inform the design of an intervention to improve recovery after delirium. Method: A rapid realist review of literature was conducted to develop an initial programme theory. Following this, a qualitative investigation of the perceived rehabilitation needs of older people who have experienced delirium during a hospital stay was conducted via semi-structured interviews with 41 key stakeholders (older people (5), carers (12), and healthcare professionals (24)). Data were analysed using a realist approach to identify what works, for whom, and in what context. This was deductively informed by the initial programme theory while also employing an inductive analysis to identify novel insights. Through an iterative, retroductive process, context-mechanism-outcome configurations (CMOCs) were coded to reflect stakeholders' views to refine the programme theory. Results: The initial programme theory highlighted the importance of cognitive and physical rehabilitation and emotional support as key domains of recovery. New CMOCs included optimisation of good medical care to manage delirium and monitoring and management of underlying medical conditions to promote recovery. Others included developing educational resources and support networks for older people and their carers to aid sense-making, and encouraging social interaction to reduce isolation and empower independent functioning. These recovery elements should be addressed in a person-centred manner that is tailored to individual needs and preferences, engages carers, integrates intervention goals into daily functioning, and ensures continuity of care. Conclusion: A refined programme theory was developed and is currently being used to design a manualised intervention to improve recovery after delirium. The acceptability of the intervention will be tested in a multi-centre, single-arm feasibility study.